A glimpse into the genotype and clinical importance of non tuberculous mycobacteria among pulmonary tuberculosis patients: The case of Ethiopia. - Alem Alemayehu; Abebaw Kebede; Sebsib Neway; Efrem Tesfaye; Betselot Zerihun; Melak Getu; Beyene Petros (PLoS ONE, 2022)
Laboratory identification of nontuberculous mycobacteria (NTM) species is not regularly performed while, they have a public health importance with a prevalence of more than 5% among pulmonary tuberculosis (PTB) patients in Ethiopia. Hence, this study aimed to identify the NTM species and their clinical significance among PTB patients. A retrospective study was conducted at the Ethiopian Public Health Institution's (EPHI's) national TB referral laboratory. Stored NTM isolates were genotyped using GenoType Mycobacterium CM/AS kit (Hain Life science, Germany). Data pertinent to the study was extracted from the EPHI's database and patients' medical records. Between January 2 & December 28 of 2017, a total of 3,834 samples were processed from 698 TB patients of whom 50% were female. Among 3,317 samples with mycobacterial culture results 7.3% were NTM and majority of them were identified from smear negative TB patients. M. simiae was the /predominant NTM among the genotyped isolates. All the studied NTM species were not clinically important however, considering the similarity of clinical and radiologic findings between NTM and MTBC infected patients, integrating NTM species identification in the routine TB laboratory diagnosis may augment clinicians' decision particularly in DR-TB patients. Additional similar prospective study with a larger sample size is recommended. Moreover, urgent improvements on patients' record keeping practice are required in the studied hospitals.